Iridium Water Oxidation Catalysts Based on Pyridine‐Carbene Alkyl‐Substituted Ligands. Issue 21 (27th September 2019) - Corbucci, Ilaria; Zaccaria, Francesco; Heath, Rachel; Gatto, Giordano; Zuccaccia, Cristiano; Albrecht, Martin; Macchioni, Alceo
Abstract: Iridium complexes bearing pyridine triazolylidene ligands with variable steric hindrance, derived by the presence of an R group (R=H, Me, Et, n Pr, i Pr, Bu, and Oct) onto the N1‐nitrogen, have been synthesized, fully characterized and tested as water oxidation catalysts (WOCs), using chemical sacrificial oxidants (CAN and NaIO4 ) or in photocatalytic experiments ([Ru(bpy)3 ]Cl2 as phosensitizer and Na2 S2 O8 as an electron acceptor). The catalytic activity is barely affected by the nature of R when WO is driven by NaIO4 (1 min −1 3 ]Cl2 /Na2 S2 O8 (TOF≈0.15 min −1 ); on the contrary, a remarkable effect is observed with CAN. Particularly, in the latter case, complexes with R=H and Me exhibit similar activity (10 min −1 <TOF<20 min −1 ), whereas all other complexes (R=Et, Pr, i ‐Pr, Bu, and Oct) are significantly more active and exhibit comparable TOFs in the range 40–130 min −1 . Thus, a marked discontinuity in performances occurs when passing from R=Me to R=Et. This can be hardly explained solely based on the previously proposed hypothesis, suggesting that an increased R‐dimension might favor the association of iridium complexes leading to the formation of highly active multimetallic species. An additional, more specific effect has to be present. It appears plausible that the steric hindrance introduced in close proximity of the iridium center, when R≥Et, hampers transfer of the hydroperoxo or peroxo moiety from iridium active species to cerium, a process that could slow down kinetics of O2 evolution. Abstract : Mind the gap : A marked discontinuity in performances is observed with pyridine triazolylidene Ir‐catalysts for water oxidation driven by CAN when passing from R=Me to R=Et substituents. Steric effects are likely responsible for the boost of activity observed for R≥Et.